Inactivation, Clearance, and Functional Effects of Lung-Instilled Short and Long Silver Nanowires in Rats - Chung, K. F.; Seiffert, J.; S. Chen; Theodorou, I. G.; Goode, A. E.; Leo, B. F.; McGilvery, C. M.; Hussain, F.; Wiegman, C.; Rossios, C.; Zhu, J.; Gong, J.; et al. (ACS Nano, 2017)
There is a potential for silver nanowires (AgNWs) to be inhaled, but there is little information on their health effects and their chemical transformation inside the lungs in vivo. We studied the effects of short (S-AgNWs; 1.5 mum) and long (L-AgNWs; 10 mum) nanowires instilled into the lungs of Sprague-Dawley rats. S- and L-AgNWs were phagocytosed and degraded by macrophages; there was no frustrated phagocytosis. Interestingly, both AgNWs were internalized in alveolar epithelial cells, with precipitation of Ag2S on their surface as secondary Ag2S nanoparticles. Quantitative serial block face three-dimensional scanning electron microscopy showed a small, but significant, reduction of NW lengths inside alveolar epithelial cells. AgNWs were also present in the lung subpleural space where L-AgNWs exposure resulted in more Ag+ve macrophages situated within the pleura and subpleural alveoli, compared with the S-AgNWs exposure. For both AgNWs, there was lung inflammation at day 1, disappearing by day 21, but in bronchoalveolar lavage fluid (BALF), L-AgNWs caused a delayed neutrophilic and macrophagic inflammation, while S-AgNWs caused only acute transient neutrophilia. Surfactant protein D (SP-D) levels in BALF increased after S- and L-AgNWs exposure at day 7. L-AgNWs induced MIP-1alpha and S-AgNWs induced IL-18 at day 1. Large airway bronchial responsiveness to acetylcholine increased following L-AgNWs, but not S-AgNWs, exposure. The attenuated response to AgNW instillation may be due to silver inactivation after precipitation of Ag2S with limited dissolution. Our findings have important consequences for the safety of silver-based technologies to human health.
Keywords: alveolar epithelial cells; bronchial hyperresponsiveness; macrophages; silver nanowires; silver sulfidation; surfactant protein d